Manajemen Penguatan Pendidikan Karakter (PPK) pada SMK Berbasis Organisasi Keagamaan Nahdlatul Ulama (NU) dan Muhammadiyyah Di Kota Bandung - Abdurozak, Dedi; Gaffar, M. Andriana; Mulyadi, Sima (CV. Media Publikasi Profesional, 2021)
The decline of national values caused by the weakness of character education. This research aims to gain an overview of the character education management in VACATIONAL HIGH SCHOOL-based Religious Organization Nahdlatul Ulama (NU) And Muhammadiyyah In Bandung City. The method used is descriptive qualitative approach method and technique of triangulation. Research results show that management education character was made based on the appropriate program of management and the functions are used. The conclusion that the management of character education in VACATIONAL HIGH SCHOOL-based Religious Organization Nahdlatul Ulama (NU) And Muhammadiyyah In Bandung City was made from planning, organizing, implementing and monitoring that in it there is the assessment process although those are not optimal.